Analysis of Blue Corona Discharges at the Top of Tropical Thunderstorm Clouds in Different Phases of Convection. Issue 6 (17th March 2022) - Dimitriadou, Krystallia; Chanrion, Olivier; Neubert, Torsten; Protat, Alain; Louf, Valentin; Heumesser, Matthias; Husbjerg, Lasse; Köhn, Christoph; Østgaard, Nikolai; Reglero, Victor
Abstract: We report on observations of corona discharges at the uppermost region of clouds characterized by emissions in a blue band of nitrogen molecules at 337 nm, with little activity in the red band of lightning leaders at 777.4 nm. Past work suggests that they are generated in cloud tops reaching the tropopause and above. Here we explore their occurrence in two convective environments of the same storm: one is developing with clouds reaching above the tropopause, and one is collapsing with lower cloud tops. We focus on those discharges that form a distinct category with rise times below 20 μs, implying that they are at the very top of the clouds. The discharges are observed in both environments. The observations suggest that a range of storm environments may generate corona discharges and that they may be common in convective surges. Plain Language Summary: Discharges in thunderstorm clouds with little or no lightning leader emissions are from cold streamers and are called corona discharges. They are thought to be generated in the upper regions of clouds that may reach into the stratosphere. Here we explore if storms with lower cloud tops may also generate these by comparing measurements of a collapsing and a developing thunderstorm environment that are part of a larger storm system. We find that the discharges are created in both environments and, therefore, may be quite common. Key Points: Corona discharges at cloud tops form a distinct type of electric discharges with rise times <20 µs in 337 nm and little activity in 777.4 nm They are generated both in developing storm cells overshooting the tropopause height and collapsing cells with remaining convective activity Most are detected by ground‐based lightning detection systems implying they are fast break‐down discharges with high currents